Integration of blue mussel (Mytilus edulis Linnaeus, 1758) with western king prawn (Penaeus latisulcatus Kishinouye, 1896) in a closed recirculating aquaculture system under laboratory conditions - Khoi, L.; Fotedar, Ravi (Elsevier BV, 2012)
Integrated farming methods, where filter feeders are used to absorb suspended particles have been used for treating nutrients and particulate wastes from prawn culture system. This study investigated the effects of integrating varying stocking densities of blue mussels (Mytilus edulis) with western king prawns (Penaeus latisulcatus) on the water quality and animals growth rates under a closed recirculating aquaculture system. The experiment was conducted using fifteen indoor recirculating systems which tested four different mussel and prawn stocking ratios (replicates of three) with a control of having prawns only. The four mussel densities and prawn biomass ratios were 0.25, 0.50, 1.00 and 2.00. Mussels in the system removed significant (P < 0.05) amounts of the total nitrogen, total suspended solids and total bacteria but did not alter the ammonia nitrogen. The dissolved inorganic nitrogen, orthophosphate and total phosphorus concentrations increased with the increasing mussel stocking densities. Integrating mussels and prawns did not affect the prawn growth and survival but mussel growth rate was positively correlated with the increasing stocking mussel densities. Nitrogen and phosphate contents in dried mussel meat in integrated environment were lower in those were integrated with prawns than in the initial mussel stocks. The study showed that mussels can grow and survive in the closed integrated culture system and effectively remove total suspended solids, total nitrogen and the total bacteria from the cultured environment. The research recommends mussel stocking density to prawn biomass ratio of 2.00 for the closed integrated recirculating aquaculture system.